2021
DOI: 10.1017/qrd.2021.7
|View full text |Cite
|
Sign up to set email alerts
|

The G protein-first activation mechanism of opioid receptors by Gi protein and agonists

Abstract: We report the G-Protein-First mechanism for activation of G protein-coupled receptors (GPCR) for the three closely subtypes of the opioid receptors (OR), h μOR, OR, and OR. We find that they couple to the inactive Gi protein-bound guanosine diphosphate (GDP) prior to agonist binding. The inactive Gi protein forms anchors to the intracellular loops of the inactive apo-μOR, apo-OR, and apo-OR, inducing opening of the cytoplasmic region to form a pre-activated state that holds Gi protein in place until agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…Overall, these two salt bridges serve as anchors that orient and position the G Gust so that the Gα–α5 helix is lined up for insertion into the cytoplasmic region of Tas1R3 (Figure and Figure S2). Strikingly, these ionic anchors are similar to ones that we found to play a crucial role in recruitment both of the Gi protein and of β-arrestin2 by opioid receptors and also for the G Gust protein by the bitter taste Tas2R4 receptor …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Overall, these two salt bridges serve as anchors that orient and position the G Gust so that the Gα–α5 helix is lined up for insertion into the cytoplasmic region of Tas1R3 (Figure and Figure S2). Strikingly, these ionic anchors are similar to ones that we found to play a crucial role in recruitment both of the Gi protein and of β-arrestin2 by opioid receptors and also for the G Gust protein by the bitter taste Tas2R4 receptor …”
Section: Resultssupporting
confidence: 70%
“…To model αβγ subunits of nucleotide-free heterotrimeric G Gust , we used our optimized Gi protein complexed with μ-opioid receptor as a template to perform homology modeling using Prime (Schrödinger). , We chose the Gi protein because there is a high sequence similarity (>∼63%) between these two heterotrimeric G protein structures.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). In previous studies for class A GPCRs, we reported that GPCRs bind strongly to their cognate GP via SB and HB interactions at all three ICLs 25 28 . However, the G i P binding mode for GABA B R is significantly different than typical class A GPCRs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Applying this procedure to the antagonist JDTic ligand in the X-ray structure leads to a structure deviating only 0.23 Å RMSD from the X-ray . This procedure led to successful ligand binding site predictions for CCR5, , GLP1R, CB1, AA3, TAS2R38, DP prostaglandin, TAS1R2/1R3 heterodimer, TAS2R4, κ-opioid receptor, and μ-opioid receptor . Based on these predictions, we identified new candidates for experimental validation.…”
Section: Methodsmentioning
confidence: 96%
“…31 This procedure led to successful ligand binding site predictions for CCR5, 32,33 GLP1R, 34 CB1, 35 AA3, 36 TAS2R38, 37 DP prostaglandin, 38 TAS1R2/1R3 heterodimer, 39 TAS2R4, 40 κ-opioid receptor, 41−43 and μ-opioid receptor. 43 Based on these predictions, we identified new candidates for experimental validation. 2.2.…”
Section: Methodsmentioning
confidence: 99%